Determinants of food security and technical efficiency among agricultural households in Nigeria - Zainab Oyetunde-Usman; Kehinde Oluseyi Olagunju (Economies, 2019)
The challenge of food security in Nigeria hinges on several factors of which poor technical efficiency is key. Using a stochastic frontier framework, we estimated the technical efficiency of agricultural households in Nigeria and tested for the significance of mean technical efficiency of food-secure and food-insecure agricultural households. We further assessed the determinants of agricultural households' inefficiencies within the stochastic frontier model and adopted a standard probit model to assess the determinants of households' food security status. The results of our analyses revealed that; on the overall, the agricultural households had a mean technical efficiency of 52%, suggesting that agricultural households have the tendency of improving their technical efficiency by 48% using the available resource more efficiently. We found that households that are food-secure are more technically efficient than food in-secure households and this was significant at one-percent. Our results provide useful insights into the role of land size and number of assets as determinants of agricultural households' food security and technical efficiency status.
Keywords: C01; Q12; Q18; 330; food security; Nigeria; technical efficiency